The Massive Fortifications of Canaanite and Judean Lachish - Ussishkin , David (Antiguo Oriente, 2025)
Lachish, a central Canaanite and Judean city in the Southern Levant during the Bronze and Iron Ages, was heavily fortified during different periods. Four different fortification systems dated to different periods have been uncovered in the extensive archaeological excavations carried out there. The present paper discusses these fortification systems, which turned Lachish into one of the strongest fortress cities of the biblical era in the Southern Levant. In several papers Yosef Garfinkel and his colleagues challenged James Starkey’s and our conclusions and interpretations regarding the character and date of the fortifications. In my view none of their suggestions are acceptable.